1989
DOI: 10.1128/jvi.63.2.579-583.1989
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus (HBV) promoters are regulated by the HBV enhancer in a tissue-specific manner

Abstract: The activities of the individual hepatitis B virus (HBV) promoters and the effects of the HBV enhancer on these promoters in several human cell types have been compared by measuring the activity and RNA levels of the linked reporter function chloramphenicol acetyltransferase. The relative promoter activities in the human HepG2 (liver), HeLa, and HS27 (fibroblast) cell lines are in the order precore greater than X greater than preS2 greater than preS1; thus, the promoters of the gene producing the largest quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(46 citation statements)
references
References 31 publications
1
42
2
Order By: Relevance
“…As we know, various HBV products are regulated by different regulatory sequences, including four promoters, that is, the preS1 promoter, preS2 promoter, X promoter, and core promoter, as well as two enhancers (enhancer I and II). In addition, two enhancers could regulate the activity of four promoters [54]. Therefore, the current data demonstrated that doxorubicin promotes HBV replication by enhancing the activity of all four promoters.…”
Section: Discussionsupporting
confidence: 50%
“…As we know, various HBV products are regulated by different regulatory sequences, including four promoters, that is, the preS1 promoter, preS2 promoter, X promoter, and core promoter, as well as two enhancers (enhancer I and II). In addition, two enhancers could regulate the activity of four promoters [54]. Therefore, the current data demonstrated that doxorubicin promotes HBV replication by enhancing the activity of all four promoters.…”
Section: Discussionsupporting
confidence: 50%
“…Previous report elucidated the existence of pregenomic/preC RNA or preS mRNA in HCC but did not identify an HBx mRNA transcript [20,21]. The promoter analysis of HBV DNA reveals that the innate promoter activity of HBx gene is actually high but the production of HBx mRNA in HBV-replicating cells is drastically repressed [31,32]. Therefore, it seems that the expression of HBx gene in human liver tissues is generally repressed but may be altered in some hepatocytes under different cellular microenvironments.…”
Section: Discussionmentioning
confidence: 93%
“…Conflicting results regarding the effect of HBxAg on transcription from the subgenomic promoters in the context of the complete transcription unit have been reported by Zhou and Yen [1990], and in two other reports the data were not shown in support of statements that the subgenomic mRNA promoters are not targets for transactivation by HBxAg Twu et al, 1989aI. Transcription under control of either subgenomic promoter is activated by enhancer(1) [Bulla and Siddiqui, 1988;De-Medina et al, 1988;Faktor et al, 1988;Antonucci and Rutter, 1989;1989;Hu and Sid-Hepatitis B Virus X-Gene Product diqui, 1991 ] which, as described above, serves as a target for transactivation by HBxAg when associated with a homologous or heterologous promoter fused to a reporter gene.…”
Section: Neweelgeeirlkvpvlcgcrhklvcspapcnfftsa Tkweegsidprzsipcrhk--mentioning
confidence: 98%